Transformation of Geography Education Through Research-Based Learning: From Indonesia for A Global Pedagogical Model - Yuli Ifana Sari; Ika Meviana; Ravinesh Rohit Prasad; Linda Maulidiah (Universitas Negeri Gorontalo, 2025)
Although Research-Based Learning (RBL) is recognized for enhancing student competencies, empirical studies testing its specific efficacy on scientific writing skills within geography education, particularly in developing countries like Indonesia, remain scarce. This gap hinders the development of pedagogical models that can effectively prepare geography students to meet their academic and professional demands. Therefore, this study evaluated the impact of an RBL model on the scientific writing skills of undergraduate geography students at an Indonesian university. Using a quasi-experimental pre-test-post-test control group design, this study involved 55 undergraduate geography students. Scientific writing ability was evaluated using an analytical rubric, and supplementary data on critical thinking and motivation were collected to enrich the analysis of the results. The analysis revealed that the experimental group that received RBL treatment demonstrated a statistically significant improvement in scientific writing skills (p 0.05) compared to the control group. This finding proves that RBL is effective in enhancing students' competence in formulating arguments, analyzing data, and presenting findings systematically. This study presents robust empirical evidence to support the integration of RBL into higher education geography curricula. The findings imply that RBL can serve as a global pedagogical model to bridge the gap between theoretical knowledge and practical application, thereby producing more competent graduate.